Trust and Power Dynamics in Children's Lived Citizenship and Participation: The Case of Public Schools and Social Work in Denmark. (16th December 2018) - Warming, Hanne
Abstract : Based on empirical data from two research projects, this article explores trust and power relations in the context of public schools and social work in Denmark and their consequences for children's lived citizenship. The analysis shows that as a group, children not only enjoy increasing recognition as citizens but they also face distrust and misrecognition due to increasing governmentalisation which threatens to overshadow the aforementioned tendencies towards inclusion and recognition, resulting in serious citizenship deficits for children in general, and for certain subgroups of children in particular, such as those positioned as 'at risk'.